Feasibility and initial assessment of a holistic neuropsychological day program for vocational rehabilitation following non-central nervous system cancer - Bloch, Ayala; Sharoni, Limor; Shany-Ur, Tal; Maril, Sari; Margalit, Daniella (Frontiers in Psychology, 2025)
ObjectivesNeuropsychological difficulties are common following non-central nervous system (CNS) cancer. Five years after treatment, up to 40% of survivors still report deficits, supported by neuropsychological tests and MRI findings. As these deficits can pose significant difficulties in finding and maintaining employment, we developed a novel vocational rehabilitation day program for non-CNS cancer survivors. The 6-month program included individual and group interventions addressing cognitive and emotional difficulties, healthy lifestyle, and job placement. In a non-randomized controlled study, we compared changes in employment status and in cognitive and emotional variables, before and after program participation.Methods46 individuals in the rehabilitation group were tested before and after participation in the program. Inclusion criteria were completion of treatment for non-CNS cancer, unemployment, and cognitive deficits shown in a neuropsychological assessment before the beginning of the program. They were compared to a control group of 15 participants who met the same inclusion criteria and were tested upon recruitment and 6 months later. Measures included employment status, a computerized cognitive test battery, and questionnaires assessing the emotional variables depression, anxiety, and fear of cancer recurrence.ResultsThe emotional variables showed greater improvement in the rehabilitation group than in the control group. There was no group by time interaction for the cognitive variables. At the second timepoint, 67% of the rehabilitation group were employed, compared to 33% of the control group.ConclusionThis first-of-its-kind program met its primary goal of supporting reintegration into the workforce among non-CNS cancer survivors with neuropsychological difficulties, alongside additional positive effects.